Regional University's Role and Place in Personnel Training System in Assessments of Employers - M. V. Boguslavsky; N. S. Ladyzhets; O. V. Sannikova; E. V. Neborsky (Высшее образование в России)
The article was prepared on the basis of a field study conducted at Udmurt State University within the “Transitive University in the Context of Global, National and Regional Challenges” Project. The article presents the results of a survey of employers on assessment the quality of training of graduates. The study focused on identifying criteria and channels for staff selection, as well as existing forms of cooperation between organizations of Udmurtia and educational institutions. The aim of the study was to clarify the role and place of Udmurt State University in the personnel training in the region. The research method was online questioning, the sample was spontaneous, the number of organizations was 192. The results of the study revealed a rather mixed picture. On the one hand, it is obvious that in general in Udmurtia organizations, rather low assessments of the quality of specialist training at Udmurt State University prevail, since most of the average grades are below 4 points. On the other hand, methods of cooperation with universities are formal and confined to organizing diploma / undergraduate practice and hiring young specialists. The low interest of employers in financing the development of new technologies and training of personnel is also obvious. In the vast majority of cases, enterprises want to get ready-made employees for their current needs without an agreed resource-consuming and long-term cooperation. Channels of communication and coordinated interaction on a long-term basis between the university and employers are most common either absent or are assessed as formal and episodic. Here, several significant reasons can be singled out such as insufficient financial resources of small organizations for working with universities; lack of time or desire on the part of organizations; lack of resources at the university for the implementation of the order; focus on “traditional industries” in the Udmurt Republic while neglecting the needs of the innovative potential development in the region. This results in the persistence of the employers' practice of “self-education in the workplace.”